#TITLE_ALTERNATIVE# - SIDDIQ (NIM 15105038); Pembimbing: Dr. Ir. S.Hendriatiningsih, MS., dan Dr. Ir. Dwi Wisayan, MIFTAHUS
Construction survey activities were defined as those activities involved the planning and implementation of surveys for the location, design, construction, operation and maintenance of civil projects and other engineering projects. One of the jobs in a construction survey of the distribution natural gas pipeline development was staking-out the points of the centreline from the map plan to the field. The accuracy of reached point planned could be calculated by implement stake-out accuracy equation using the data specification of the Electronic Total Station (ETS) and the deviation standard of know point. The data that used to calculated stake-out accuracy is polygon measurement data as a know point and staking-out of point design from plan map. The calculation were performed comprising horizontal angle, staking-out distance, the calculation of deviation standard of reached point planned, lenght of pipe prediction and analyzed of the deviation standard of reached point based on staking out accuracy requirement. Based on calculations performed, the deviation standard of reached point planned was smaller than the standard accuracy of the stake and there was a tendency that the accuracy was less accurately as the staking distance took longer from the starting point. The staking accuracy calculation method was advandtageous for stake planning and another applied construction survey activity.